Efektivitas beberapa varietas dan pupuk mikoriza terhadap hasil jagung manis (Zea mays saccharata sturt) - Paridawati, Ika; Aminah, Iin Siti; Amir, Nurbaiti; Anugerah, Deni (Jurnal Agrotek Ummat, 2022)
This study aims to determine the best variety and dosage of mycorrhizal fertilizer to the yield of sweet corn (Zea mays saccharata Sturt.).  This research was conducted on farmer’s land in Dusun Beringin Makmur I, Kecamatan Rawas Ilir, South Musi Rawas Regency, South Sumatra, from October to December 2020. This study used an experimental method with a split plot design consisting of 9 treatment combinations and 3 replications.  The first factor (Main-plot) of variety (V), namely V1 = Talenta; V2 = Bonaza; V3 = Master Sweet, while the second factor (Sub-plot) is mycorrhiza fertilizer (M), namely M0 = without mycorrhiza fertilizer; M1 = 30 g per plant; M2 = 40 g per plant.  Observational in this study included the cob of lenght (cm), cob of diameters (cm), cob of weight per plant (g) and cob of weight per plot (kg).  The results showed that Bonanza variety gave the best yield on sweet corn, 40 g mycorrhizal fertilizer per plant gave the best yield on sweet corn and tabulated combination of variety and mycorhiza fertilizer 40 g per plant gave the highest yield of sweet corn at 4.22 kg per plot equivalent to 16.88 ton ha-1.